Study on Mineral Distribution of Peat Soil in Northeast China - Nie1, Lei; Su1, Zhan-Dong; Xia2, Jing; Lv1, Yan; Li1, Ze-Chuang (Asian Journal of Chemistry, 2013)
Peat soil is a special kind of humus soil that is abundant with organic matter, minerals and plant fibers. The plant fibers and organic matter are separated, respectively by using the rinsing method and the chemical methods. Dry soil samples are obtained to analyze the distribution of minerals using X-ray powder diffraction method with scanning electron microscopy and loss on ignition test. The main minerals found in the peat soil are clay minerals (illite, chlorite and kaolinite) and gravel soil minerals (quartz, plagioclase and mica). Illite is significantly reduced at 1.2 and 2.2 m depth. It is also partly transformed into kaolinite because of the impact of humic acid and internal porosity. Quartz and mica have similar distribution patterns that are significantly increased at 1.2 and 2.2 m depth on account of the tiny, but abundant, root flocculent structure. Plagioclase is distributed similar to that of illite.